learning media to increase students' interest in learning at buddhist sunday school in vihara maitri ratna giriwoyo - Ardianto, Ryo; Suyatno, Tri (Pendidikan Dasar dan Manajemen Pendidikan, 2025)
This research aims to determine student interest at SMB Vihara Maitri Ratna by using learning media. Buddhist Sunday School (SMB) includes non-formal education carried out at monasteries or cetiya. During the learning process in class, of course there is a problem, namely students who are less enthusiastic and don't understand what the teacher is teaching. So teachers must be able to create a comfortable classroom atmosphere, for this reason a teacher and students must work to create it. In this case, improving learning carried out in the classroom is important for teachers to increase interest in learning among their students, namely by teachers carrying out learning using interactive, interesting and creative learning media in delivering the material so that the students they teach can understand what is being conveyed by them. the teacher. Learning media are tools or means used to convey information, concepts or knowledge to students. The use of learning media aims to increase students' understanding, skills and interest in learning. It is hoped that it can attract students' interest in learning and motivate students to study Buddha Dhamma.